THE INFLUENCE OF HYPOLIPIDEMIC THERAPY ON NITROUS OXIDE SYSTEM IN PATIENTS WITH ISCHEMIC HEART DISEASE ASSOCIATED WITH NONALCOHOLIC STEATOHEPATITIS - Скрипник, І.М.; Маслова, Г.С.; Щербак, О.В. (World of Medicine and Biology, 2017)
Results of own research are presented in the article. It was demonstrated, that in patients with ischemic heart disease (IHD) associated with non-alcoholic steatohepatitis (NASH), activity of alanine aminotransferase (ALT), aspartate aminotransferase (AST) and gamma-glutamyltranspeptidase (GGTP) increased 3.8; 2.6 and 3.2 fold accordingly on the background of atherogenic dyslipidemia. These changes were accompanied by such alterations in nitrous oxide system as increase of total nitric oxide synthase activity 2.3 fold with simultaneous nitrites decrease 1.9 fold in comparison with norm. Combination of rosuvastatin in average therapeutic doses with ursodeoxycholic acid (UDCA) and L-carnitine led to normalization of lipid metabolism indexes with achieving the target level of low-density lipoprotein cholesterol below 1.8 mmol/l in 1 month of therapy. Decrease of total nitric oxide synthase activity 2.3 fold and increase of nitrites 1.9 fold in blood serum were observed in the same time. Thus, additional prescription of UDCA and L-carnitine can be recommended in patients with IHD and associated NASH to optimize hypolipidemic therapy.
Keywords: ischemic heart disease; nonalcoholic steatohepatitis; nitric oxide; dyslipidemia